(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Circadian rhythm (biological rhythm) disorders alter the body's natural sleep-wake cycles and have been associated with mood fluctuations, cardiovascular problems and cognitive degeneration. Notable disorders that result from an imbalance between an individual's internal circadian rhythms and external factors, such as light exposure and social responsibilities, can lead to conditions like delayed sleep-wake phase disorder (DSPD), advanced sleep phase syndrome (ASPD) and Shift work disorder (SWSD). The pineal gland secretes melatonin, a hormone that promotes sleep and indicates darkness to stabilize the circadian rhythms. This study explores the impact of melatonin on the suprachiasmatic nucleus (SCN), the brain's central clock, and its potential therapeutic applications for disorders that disrupt the circadian rhythm. Melatonin treatment lowers sleep onset latency (SOL), advances sleep-wake cycles in individuals with DSPD, and enhances morning alertness, according to clinical investigations. It improves the quality of sleep, which has some advantages for ASPD, especially in older persons. Melatonin lessens daytime drowsiness, eases insomnia, and helps sleep patterns adapt to work schedules for SWSD. In addition to discussing ideal dosage, possible adverse effects, and the necessity of customized care, this review highlights the significance of more research on the long-term safety of melatonin, medication interactions, and its application in combination therapy for disorders of the circadian rhythm.